IFN-α induced systemic lupus erythematosus complicated with hemophagocytic lymphohistiocytosis: a case report and literature review - Zeng, Zhipeng; Tu, Wei; Ji, Bai; Liu, Jie; Huang, Kecheng; Nie, Daan; Yang, Liu (Frontiers in Immunology, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is a severe and life-threatening hyperinflammatory condition characterized by excessive activation of macrophages and T cells and resulted in multi-organ dysfunction. HLH can be a primary disease or secondary to infections, malignancy, and some autoimmune diseases, including adult-onset Still’s disease (AOSD) and systemic lupus erythematosus (SLE). However, it is rare for HLH to occur as a secondary condition to drug-induced lupus erythematosus (DILE). In this report, we present a case of HLH as an unusual complication during SLE treatment in a 31-year-old male patient. The patient initially suffered from active chronic hepatitis B (CHB) and was treated with pegylated INFα-2b (Peg-INFα-2b), tenofovir disoproxil and lamivudine. After 19 months, CHB obtained biochemical and virological response with HBsAg positive to HBsAb. The patient developed fever, headache, and cytopenia after Peg-INFα-2b treatment for 33 months, and laboratory studies revealed that ANA and anti dsDNA were positive. He displayed 5 features meeting the HLH-2004 criteria for diagnosis including fever, pancytopenia, hyperferritinemia, high levels of soluble CD25, and hemophagocytosis on bone marrow biopsy. The patient was initiated with a combination treatment of intravenous methylprednisolone pulse therapy, oral cyclosporine, and etoposide (VP-16), which was followed by a course of oral prednisolone, intravenous cyclophosphamide pulse therapy, and entecavir with complete response. To our knowledge, this is the first report of IFN-α induced SLE complicating with HLH. Physicians should consider the potential autoimmune side effects of IFN-α therapy and be alert to insidious HLH in patients diagnosed with SLE.